Implementasi Fungsi Hash dalam Kriptografi Modern untuk Enkripsi Data Satu Arah - Winanda, Mirza; Defrianti, Serli; Nabila, Wulan; Rikarni, Rikarni; Alfarizhi, Habieb (JIKUM: Jurnal Ilmu Komputer, 2025)
Cryptography is the science and art used to maintain data privacy. In its development, modern cryptographicalgorithms work by processing data in the form of a series of bits. One important approach in cryptography is the useof a one-way hash function (one-way hash function), which is able to change data into a fixed representation thatcannot be returned to its original form.This paper discusses the implementation of hash functions in modern cryptography for the one-way encryptionprocess. The hashing application is developed using the Python programming language with the hashlib library and aTkinter-based GUI interface. This application allows users to enter text, select a hash algorithm such as MD5, SHA1, SHA-256, SHA-512, and HSE, and get the hash results directly. Tests were carried out on several algorithms totrigger differences in the length and complexity of the results.The main characteristic of a one-way hash function is that two different messages will always produce different hashvalues. The test results show that each algorithm produces a unique hash value for a given input, with varying lengthsdepending on the algorithm used. SHA-512 produces the longest hash and is considered the most secure among otheralgorithms.